2015
DOI: 10.1021/acs.molpharmaceut.5b00054
|View full text |Cite
|
Sign up to set email alerts
|

Reductively Responsive Hydrogel Nanoparticles with Uniform Size, Shape, and Tunable Composition for Systemic siRNA Delivery in Vivo

Abstract: To achieve the great potential of siRNA based gene therapy, safe and efficient systemic delivery in vivo is essential. Here we report reductively responsive hydrogel nanoparticles with highly uniform size and shape for systemic siRNA delivery in vivo. “Blank” hydrogel nanoparticles with high aspect ratio were prepared using continuous particle fabrication based on PRINT (particle replication in nonwetting templates). Subsequently, siRNA was conjugated to “blank” nanoparticles via a disulfide linker with a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…47 Our previous work demonstrated that cationic hydrogel particles were able to efficiently deliver siRNA to cytosol, resulting in efficient gene silencing. 48,49 Furthermore, Fromen et al demonstrated significanlty higher lung and systemic antibody titers when cationic particles were used to deliver ovalbumin, as compared to anionic particles. 50 Therefore, amine groups on the NP surface were used to conjugate cysteine labeled SIINFEKL peptide via reduction sensitive, heterobifunctional linkers SPDP or NHS-PEG(2k)OPSS in a two step-process (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…47 Our previous work demonstrated that cationic hydrogel particles were able to efficiently deliver siRNA to cytosol, resulting in efficient gene silencing. 48,49 Furthermore, Fromen et al demonstrated significanlty higher lung and systemic antibody titers when cationic particles were used to deliver ovalbumin, as compared to anionic particles. 50 Therefore, amine groups on the NP surface were used to conjugate cysteine labeled SIINFEKL peptide via reduction sensitive, heterobifunctional linkers SPDP or NHS-PEG(2k)OPSS in a two step-process (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…48,5355 Due to the versatility of the PRINT platform, it has been employed to study the impact of various particle parameters in a biological system such as biodistribution of intravenously administered NPs as well as lymphatic trafficking of particles after intramuscular administration. 56,57 Utilizing immunologically inert materials to mimic size, shape, and surface functionality of pathogens, PRINT provides an excellent platform to engineer subunit vaccines investigating various combinations of antigens and adjuvants to tune the immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PEG modified with pyridyl disulphide could be directly conjugated to siRNA containing a thiol group, since a pyridyl disulfide will readily undergo an interchange reaction with a free sulfhydryl to yield a single mixed disulfide product 33. , 34. .…”
Section: Resultsmentioning
confidence: 99%
“…A different polymerization technique was the PRINT (particle replication in non-wetting templates) particle fabrication technique, which is characterized by a higher degree of difficulty, but by complete, orthogonal control over particle characteristics, and an easiness of scaling up [33]. Ma et al proposed a PRINT particle fabrication technique for the production of hydrogel nanoparticles conjugated with siRNA (short interfering RNA, highly used for gene therapy) [34]. The same technique was used by Kai et al for the nano-encapsulation of cisplatin, a cytotoxic drug used in therapy against a wide variety of cancers [33].…”
Section: Polymerization Methodsmentioning
confidence: 99%